Aerobic exercise reduces triglycerides by targeting apolipoprotein C3 in patients with coronary heart disease. Issue 1 (21st December 2018) - Wang, Yating; Shen, Li; Xu, Danyan
Abstract : Background: Aerobic exercise, which has been shown to have beneficial effects on plasma lipids, has been recommended as an effective measure to improve the prognosis of individuals with coronary heart disease (CHD). Apolipoprotein C3 (apoC3) is associated with hypertriglyceridemia and is therefore closely related to CHD. Hypothesis: We measured apoC3 concentration change in patients with CHD before and after long‐term aerobic exercise. Methods: Thirty‐eight patients with coronary heart disease were randomly assigned to a non‐exercise group (19 patients) or exercise group (19 patients). Both groups received essential drugs for CHD. The non‐exercise group was kept sedentary while the exercise group performed moderate‐intensive aerobic exercise for 8 weeks. Lipid levels and apoC3 levels were measured on the first day and 8 weeks later. Results: Exercise for 8 weeks led to a significant decrease in concentration of triglyceride and apoC3 compared with the baseline. Triglyceride concentration changes were positively associated with apoC3 level changes. Conclusions: Aerobic exercise can improve the lipid profile. It is effective in decreasing triglycerides by targeting apoC3 levels in patients with coronary heart disease.